2012
DOI: 10.1136/jnnp-2012-302468
|View full text |Cite
|
Sign up to set email alerts
|

MUltiple Sclerosis and Extract of Cannabis: results of the MUSEC trial

Abstract: Objective Multiple sclerosis (MS) is associated with chronic symptoms, including muscle stiffness, spasms, pain and insomnia. Here we report the results of the Multiple Sclerosis and Extract of Cannabis (MUSEC) study that aimed to substantiate the patient based findings of previous studies. Patients and methods Patients with stable MS at 22 UK centres were randomised to oral cannabis extract (CE) (N¼144) or placebo (N¼135), stratified by centre, walking ability and use of antispastic medication. This double bl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
175
0
11

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 216 publications
(189 citation statements)
references
References 25 publications
3
175
0
11
Order By: Relevance
“…Conversely, dronabinol might have a slight potentially negative effect in patients with higher EDSS scores. One possible explanation for these findings is that cannabinoids have been shown to reduce muscle stiffness 2,26,27 and, although an antispasticity effect might improve function at lower levels of disability, if walking is compromised by weakness, dronabinol might reduce muscle tone to the point where muscle power becomes affected and walking is more difficult. This side effect is well known with agents such as baclofen.…”
Section: Further Analysesmentioning
confidence: 99%
See 2 more Smart Citations
“…Conversely, dronabinol might have a slight potentially negative effect in patients with higher EDSS scores. One possible explanation for these findings is that cannabinoids have been shown to reduce muscle stiffness 2,26,27 and, although an antispasticity effect might improve function at lower levels of disability, if walking is compromised by weakness, dronabinol might reduce muscle tone to the point where muscle power becomes affected and walking is more difficult. This side effect is well known with agents such as baclofen.…”
Section: Further Analysesmentioning
confidence: 99%
“…(15) 162 (2) 248 (27) 129 (9) 216 (36) 119 (10) 193 (42) 108 (12) 172 (46) 95 (13) 147 (52) 87 (14) 3 (88) 8 (176) Placebo FIGURE 3 Kaplan-Meier estimates of the probability of progression on the EDSS in the two treatment groups, confirmed after 6 months within the study period. The numbers at risk (cumulative number of censored observations) are given.…”
Section: Prescribed Dose Of Trial Medicationmentioning
confidence: 99%
See 1 more Smart Citation
“…Os naxibimols, os preparados com THC/CBD e o extrato de cannabis apresentaram resultados conflitantes, e embora não seja possível concluir de forma definitiva quanto à sua eficácia, os dados sugerem que esta pode ser uma opção terapêutica em pacientes que não responderam aos tratamentos convencionais 7,8,9,10,11 .…”
Section: Canabinoides Na Esclerose Múltiplaunclassified
“…They concluded that while there was no improvement shown when assessing spasticity on the Ashworth scale, there was an improvement in subjective perception of spasticity and also other secondary outcomes. In 2012, the Multiple Sclerosis and Extract of Cannabis trial concluded that the rate of relief of muscle stiffness in patients with MS patients after 12 weeks of therapy was doubled with the same cannabis extract compared with placebo [13].…”
Section: Msmentioning
confidence: 99%